A computational model for estimating the performance of flat plane low concentration systems - Rolando Soler-Bientz; F. Gomez-Castro (2004)
The implementation of PV systems is one of the feasible alternatives to meet the energy supply in communities far from the conventional electric grid. Several studies have shown that a flat plane concentrator can produce better electrical behaviour in a PV system, due to the reduction of the effective panel surface needed for the operation of the system. As the cost of a PV system is strongly conditioned by the cost of the PV panels, it can lead to an increase of the PV market. This work describes the computational model developed to represent the concentration pattern over a collector, generated by a flat plane reflector. A useful 3D representation of the system has been programmed to visualize the concentration system. The computational model was developed in Mathematica Programming Language Environment. The simulation tool created shows that Mathematica is a quick and powerful tool to represent the low-concentrating photovoltaic systems.